Increased expression of activation-induced cytidine deaminase is associated with anti-CCP and rheumatoid factor in rheumatoid arthritis - Xu, Xin (2009)
Rheumatoid arthritis (RA) is associated with higher levels of autoantibodies and IL-17. Here, we investigated if ectopic lymphoid follicles and peripheral blood mononuclear cells (PBMCs) from RA patients exhibit increased activation-induced cytidine deaminase (AID), and if increased AID is correlated with serum levels of autoantibodies and IL-17. The results of immunohistochemical staining showed that organized germinal centers were observed in 6 of the 12 RA synovial samples, and AID(+) cells were found almost exclusively in the B-cell areas of these follicles. Aggregated but not organized lymphoid follicles were found in only one OA synovial sample without AID(+) cells. Significantly higher levels of AID mRNA (Aicda) detected by RT-PCR were found in the PBMCs from RA patients than PBMCs from normal controls (p<0.01). In the PBMCs from RA patients, AID was expressed predominately by the CD10(+)IgM(+)CD20(+) B-cell population and the percentage of these cells that expressed AID was significantly higher than in normal controls (p < 0.01). Aicda expression in the PBMCs correlated significantly and positively with the serum levels of rheumatoid factor (RF) (p ≤ 0.0001) and anti-cyclic citrullinated peptide (CCP) (p = 0.0005). Serum levels of IFN-γ (p = 0.0005) and IL-17 (p = 0.007), but not IL-4, also exhibited positive correlation with the expression of AID. These results suggest that the higher levels of AID expression in B cells of RA patients correlate with, and may be associated with the higher levels of T helper cell cytokines IFN-γ and IL-17, leading to the development of anti-CCP and RF.